Oral Microbiome Signatures in Diabetes Mellitus and Periodontal Disease. (June 2020) - Matsha, T.E.; Prince, Y.; Davids, S.; Chikte, U.; Erasmus, R.T.; Kengne, A.P.; Davison, G.M.
Disturbances in the oral microbiome are associated with periodontal disease initiation and progression and diabetes mellitus (DM), but how this contributes to the cause-and-effect relationship between periodontal disease and DM is poorly understood. We examined the bacterial composition in plaque samples from 128 South Africans with periodontal disease across glycemic statuses using 16S rDNA sequencing of regions 2, 3, 4, 6-7, 8, and 9. Of the 9 phyla identified, Firmicutes, Proteobacteria, Bacteroidetes, Fusobacteria, and Actinobacteria made up >98%. Fusobacteria and Actinobacteria were significantly more abundant in subjects with diabetes, while Proteobacteria were less abundant. However, in the presence of gingival bleeding and DM, as compared with DM without gingival bleeding, Actinobacteria were markedly reduced while Bacteroidetes were more abundant. In contrast, no differences in Actinobacteria or Bacteroidetes abundance were observed between DM with and without pocket depth (PD) ≥4 mm. At the genus level, similar changes in relative abundance were observed in the presence of DM and periodontal disease. Our findings remained in conditional logistic regression models adjusted for age, sex, waist circumference, and the 5 most dominant phyla. For example, Actinobacteria significantly increased the odds of diabetes by 10% in subjects with gingival bleeding, while Fusobacteria increased this odd by 14%; yet, among subjects with PD ≥4 mm, Fusobacteria decreased the odds of DM by 47%. Our findings have confirmed the alterations in the composition of the oral microbiota across glycemic statuses as well as different stages of periodontal disease. However, it is not clear whether these differences were the consequence of hyperglycemia or the presence of periodontal diseases. Therefore, we recommend further investigations in a longitudinal study design.